Internet of things (IoT): a technology review, security issues, threats, and open challenges - Alaa Ahmed Abbood; Qahtan Makki Shallal; Mohammed A. Fadhel (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Internet of things (IoT) devices are spread in different areas such as e-tracking, e-commerce, e-home, and e-health, etc. Thus, during the last ten years, the internet of things technology (IoT) has been a research focus. Both privacy and security are the key concerns for the applications of IoT, and still face a huge number of challenges. There are many elements used to run the IoT technology which include hardware and software such as sensors, GPS, cameras, applications, and so forth. In this paper, we have analyzed and explain the technology of IoT along with its elements, security features, security issues, and threats that attached to each layer of IoT to guide the consideration of researchers into solve and understand the most serious problems in IoT environment.